Effect of Family Hope Program on Maternal Health Behavior and Children Under Five Nutritional Status in Poor Families, Jombang, East Java - Rosalina, Sintya; Sulaeman, Endang Sutisna; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Family Hope Program, or internationally referred to as Conditional Cash Transfer (CCT), is a government poverty allevation initiative by provision of conditional cash money that induces healthy behavior so as to achieve strong generation. This study sought to examine the effect of Family Hope Program on maternal health behavior and children under five nutritional status in poor families, Jombang, East Java.Subjects and Method: This was an analytic observational study with retrospective cohort design. This study was conducted in Jombang District, East Java, from November to December 2017. A total sample of 210 mothers and their children under five were selected for this study by fixed exposure sampling. The dependent variables were maternal health behavior and child nutritional status. The independent variables were birthweight, history of illness, maternal education, family income, family support, government Family Hope Program,  and access to health service. The data were collected by maternal and child book record and questionnaire. The data were analyzed by path analysis.Results: The likelihood of good nutritional status of children under five increased with good nutritional intake (b= 1.9; 95% CI= 1.1 to 2.8; p <0.001), normal birthweight (b= 2.5;  95% CI= 0.9 to 4.1; p= 0.002), rare frequency of illness (b= 1.3; 95% CI= 0.5 to 2.1; p= 0.001), and strong family support (b= 1.5; 95% CI= 0.6 to 2.3; p<0.001). The likelihood of maternal healthy behavior increased with Family Hope Program (b= 4.1; 95% CI= 3.1 to 5.0; p <0.001) and higher maternal education (b= 1.9; 95% CI= 0.9 to 2.8; p<0.001). Good nutritional intake increased with maternal healthy behavior (b= 0.4; 95% CI= - 0.04 to 0.85; p = 0.074) and strong family support (b= 0.6; 95% CI = 0.2 to 1.1; p= 0.004).Conclusion: The likelihood of good nutritional status of children under five increases with good nutritional intake, normal birthweight, no history of illness over the past three months, and strong family support. Family Hope Program induces maternal health behavior, increases child nutritional intake, and eventually improves child nutritional status.Keywords: child nutritional status, maternal health behavior, Family Hope ProgramCorrespondence: Sintya Rosalina. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: sintya.rosalina@gmail.com. Mobile 085732761747.Journal of Maternal and Child Health (2018), 3(1): 33-43https://doi.org/10.26911/thejmch.2018.03.01.04